Dual Road Approach of the ‘Suspended Dead’ Brand XYZ Shampoo’s Social Media to Create Assumed Brand Awareness - Mohammad Ichsan (Avant Garde, 2018)
In early 2017, XYZ brand owners revived its ‘suspended dead’ brand back to the market. The company decide to utilized Social Media as the initial channel to create Brand Awareness. This study uses a qualitative approach with descriptive methods to describe its implementation and explain the analytical data based on their Social Media performance, also using exploratory methods for more creative in-depth and broad understanding on the issue. The results of this study indicate that the application of the Dual Road approach, which consists of the 'Non-Toll Road' and the 'Toll Road' approach by the XYZ brand resulted in significantly different achievements in the effort to create assumed Brand Awareness.